Heterogeneous Distribution of Erucic Acid in Brassica napus Seeds - Lu, Shaoping; Aziz, Mina; Sturtevant, Drew; Chapman, Kent D.; Guo, Liang (Frontiers in Plant Science, 2020)
Brassica napus (B. napus) is the world’s most widely grown temperate oilseed crop. Although breeding for human consumption has led to removal of erucic acid from refined canola oils, there is renewed interest in the industrial uses of erucic acid derived from B. napus, and there is a rich germplasm available for use. Here, low- and high-erucic acid accessions of B. napus seeds were examined for the distribution of erucic acid metabolites and the gene transcripts encoding the enzymatic pathways for its incorporation into triacylglycerols (TAGs) across the major tissues of the seeds. In general, the results indicate that a heterogeneous distribution of erucic acid across B. napus seed tissues was contributed by two isoforms (out of six) of FATTY ACYL COA ELONGASE (FAE1) and a combination of phospholipid:diacylglycerol acyltransferase (PDAT)- and diacylglycerol acyltransferase (DGAT)-mediated incorporation of erucic acid into TAGs in cotyledonary tissues. An absence of the expression of these two FAE1 isoforms accounted for the absence of erucic acid in the TAGs of the low-erucic accession.